Claude Lefort's Political Philosophy Democracy, Indeterminacy, Institution - Di Pierro, Mattia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book proposes a new interpretation of Claude Lefort's thought focusing on his phenomenological method. Although all scholars recognize the influence of Merleau-Ponty, so far no one has demonstrated the fundamental coherence between Merleau-Ponty's theory and the main concepts proposed by Lefort; in particular between the concept of institution and the definitions of social and democracy. If Merleau-Ponty uses the idea of institution to think beyond the division between subject and object, to think together continuity and difference, permanence and change, this same concept allows Lefort to understand society as both conflict and unity. From this starting point, this study will attempt to clarify Lefort's concept of the political and his interpretations of modernity, humanism, and the work of Niccolò Machiavelli. These very concepts will show the difference from structuralism, Michel Foucault's contemporary theory and theories of immanence. At the same time this study highlights aninternal tension in Lefort's own thinking: between autonomy and experience, institution and insurgence. Mattia Di Pierro is a Post-Doc researcher at the Philosophy Department of the University of Milan, Italy. His research mainly concerns contemporary political thought, theories of democracy and of modernity. He is the author of L'esperienza del mondo: Claude Lefort e la fenomenologia del politico (ETS 2020) and numerous articles on history of political thought and political philosophy.
Chapter 1: Socialisme ou Barbarie -- Chapter 2: Society, Reality, Alienation and Ideology -- Chapter 3: The modern symbolic revolution -- Chapter 4: The interpretation of Machiavelli -- Chapter 5: The theory of the political -- Chapter 6: Democracy and Totalitarianism -- Chapter 7: Conclusions.
Keywords: Political science -- Philosophy; Political science; Critical theory; World politics; Political Philosophy; Political Theory; Critical Theory; Political History